Modelling microstructure evolution, creep deformation and damage in Type 316H stainless steel - Petkov, M (2020)
The current Advanced Gas-cooled Reactors (AGR) in the UK are approaching their design life. The reactor operator, EDF Energy, is seeking to extend their life due to ecological and financial reasons. One challenge to plant life-extension is the accurate prediction of high-temperature deformation and failure of Type 316H stainless steel, used in components of the reactor boiler section. Under the operating conditions of these components (470-650°C; 10-300 MPa), creep and cyclic plasticity alter the material’s microstructure and failure response. Empirical models are used in industry to predict the deformation and damage response of Type 316H. Predictions can be in poor agreement with plant-recorded/experimental deformation response under complex loading histories. Furthermore, the models are deficient in capturing the sensitivity of the creep damage process to the microstructural state of the material. The overall aim of this research is to improve the understanding of high-temperature deformation and failure response of Type 316H under common plant conditions in order to make realistic life predictions. This is achieved through development of micromechanical models for deformation and damage, employed within polycrystalline modelling frameworks.